FUNDAMENTAL PRINCIPLES AND DEVELOPEMENT OF FEMINIST THEORY (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article provides a comprehensive examination of the fundamental principles and historical development of feminist theory. Feminist theory is a diverse field of study that critically analyzes the experiences, perspectives, and struggles of women and other marginalized genders. The core principles explored include the personal as political, recognition of gender-based oppression and inequality, challenging patriarchal power structures, intersectionality, and the pursuit of emancipation and social transformation. The article traces the evolution of feminist theory through its key historical phases, from first-wave to fourth-wave feminism. It discusses how feminist theory has expanded its scope and incorporated insights from various disciplines to address an increasingly diverse range of gender-related issues and inequities. The article concludes by highlighting the ongoing relevance and impact of feminist theory in driving meaningful progress towards gender equality and social justice.